Pengaruh Variasi Konsentrasi Ekstrak Bunga Kamboja (Plumeria alba) dalam Lotion sebagai Repellent Terhadap Daya Tolak Nyamuk Aedes sp - Niken Kriswandari; Haryono Haryono; Adib Suyanto (Poltekkes Kemenkes Yogyakarta, 2015)
Dengue Hemorrhagic Fever (DHF) is a disease caused by virus and transmitted by Aedes sp. mosquitoes. Most areas in Indonesia is endemic where frequency of outbreaks is escalating and the disease is one of major health problems in Indonesia. One way to avoid mosquito bites is by using repellent. However, repellent with active ingredients made from synthetic chemicals have side effects that harmful for human health. Therefore, it is a necessity to seek safer natural ingredients, one of which is kamboja flowers (Plumeria alba). The purpose of this study is to determine the effect of extract concentration variation of that flower in the lotion as a repellent and to find the most effective one. The research method used was an experiment with post test onlywith control group design. Kamboja flower extract concentration added into the lotion were 20 %,30 %, and 40 %. The results were analyzed by statistical tests using two way anova and LSD at 95 % level of confidence. The results showed that the extract concentration variation significantly gave different repellence power (p=0,039) to Aedes sp. and 40 % was found as the most effective concentration. The repellence power of this concentration at the first and the fifth hour of observation were 83,81 % and 3,52 %, respectively.